Expression and cellular distribution of ubiquitin in response to injury in the developing spinal cord of Monodelphis domestica. - Natassya M Noor (Public Library of Science (PLoS), 2013)
Ubiquitin, an 8.5 kDa protein associated with the proteasome degradation pathway has been recently identified as differentially expressed in segment of cord caudal to site of injury in developing spinal cord. Here we describe ubiquitin expression and cellular distribution in spinal cord up to postnatal day P35 in control opossums (Monodelphis domestica) and in response to complete spinal transection (T10) at P7, when axonal growth through site of injury occurs, and P28 when this is no longer possible. Cords were collected 1 or 7 days after injury, with age-matched controls and segments rostral to lesion were studied. Following spinal injury ubiquitin levels (western blotting) appeared reduced compared to controls especially one day after injury at P28. In contrast, after injury mRNA expression (qRT-PCR) was slightly increased at P7 but decreased at P28. Changes in isoelectric point of separated ubiquitin indicated possible post-translational modifications. Cellular distribution demonstrated a developmental shift between earliest (P8) and latest (P35) ages examined, from a predominantly cytoplasmic immunoreactivity to a nuclear expression; staining level and shift to nuclear staining was more pronounced following injury, except 7 days after transection at P28. After injury at P7 immunostaining increased in neurons and additionally in oligodendrocytes at P28. Mass spectrometry showed two ubiquitin bands; the heavier was identified as a fusion product, likely to be an ubiquitin precursor. Apparent changes in ubiquitin expression and cellular distribution in development and response to spinal injury suggest an intricate regulatory system that modulates these responses which, when better understood, may lead to potential therapeutic targets.